Improving smash accuracy in badminton through progressive drill training: sports action research - Muhammad Rizky Putra Hadi; Mashud Mashud (Universitas Sriwijaya, 2026)
Research Problems: Smash accuracy is a fundamental skill in badminton that requires precise and structured training methods. Research Objectives: This study aims to improve the smash accuracy of badminton athletes through the Progressive Drill Training approach. Methods: This research employed a Sports Action Research design with a Participatory Action Research (PAR) approach conducted in three cycles. The subjects were eight PB Berkat Abadi Banjarmasin badminton athletes (6 boys and 2 girls), aged 14–17 years, selected through purposive sampling. The Progressive Drill Training program consisted of three progressive levels: Level 1 (smash with controlled feeding), Level 2 (smash with variation in direction and timing), and Level 3 (smash in game-like situations). Smash accuracy was measured using the Modified Badminton Smash Accuracy Test with 10 attempts per testing session. Data were analyzed descriptively and comparatively across cycles to track improvement. Results: The findings showed consistent improvement in smash accuracy across all cycles. The average score increased from 11.75 points at baseline to 12.74 points in Cycle 2, and further to 13.45 points in Cycle 3. All athletes demonstrated progressive improvement with a 100% participation rate and positive responses to the training program. Conclusion: Progressive Drill Training effectively enhances athletes’ timing, coordination, rhythm, and smash accuracy. This method can be recommended as a structured and practical training approach for developing smash skills in badminton. Future research may expand the sample size, compare different training methods, or explore its application to other technical skills in badminton.